Implementasi Metode Eksperimen dalam Meningkatkan Prestasi Belajar IPA - Warsiki, Ni Made (Jurnal Penelitian dan Pengembangan Pendidikan, 2018)
This research was conducted in Class IX-13 SMP Negeri 2 Singaraja in odd semester of 2016/2017, with condition of learning achievement of IPA not yet fulfill KKM. The purpose of this classroom action research is to improve students' learning achievement through experimental methods. The method of data collection through the test of learning achievement, which then analyzed by using descriptive method quantitative. The data were presented in the form of average learning achievement and learning mastery procession. The results obtained from this study is the students' learning achievement initially averaged only 73.56 with mastery learning 52.78%, then after the implementation of Cycle I student achievement increased to an average of 79.22 with learning completeness reached 83.33 %. Cycle II also happened improvement of student achievement reach 79,76 and learning comprehension 86,11%. The conclusion obtained from this research is Implementation of experimental method can improve student achievement in class IX-13 odd semester, academic year 2016/2017.